Pengaruh Kepribadian Lima Besar Terhadap Intensi Berwirausaha Pada Mahasiswa Psikologi Universitas Negeri Jakarta: The Association between Big Five Personality toward Student's Entpreunership Intention - Erik, Erik (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2020)
There are several factors that can influence a person to become an entrepreneur. One of them is the personality factor. The purpose of this study was to determine the influence of the top five personality traits on entrepreneurial intentions in psychology students at the Universitas Negeri Jakarta. The methodology used in this research is quantitative by using regression analysis. The sample in this study was 136 final year psychology students at the State University of Jakarta. The instruments used in this study were the entrepreneurial intention instrument and the Big Five Inventory Scale Indonesian version. The results showed that there was an effect of agreeableness personality dimensions on entrepreneurial intentions. The coefficient value (Adjusted R square) is 0.058. This means that the top five personality dimensions contribute 5.8% to entrepreneurial intentions.